Riesgos físicos y ergonómicos para la seguridad y salud ocupacional de los trabajadores del laboratorio Nes Larvas del cantón, Jama - Beltrán Vélez, Karen Selena (2020)
This investigation was carried out within the facilities of the Nes Larvas laboratory, located at the El Matal site, Jama canton, province of Manabí, which aimed to evaluate the physical and ergonomic risks found in that place. Information was collected to diagnose the current situation in which the laboratory finds itself, in order to know its administrative structure and the processes they carry out. After this, the physical and ergonomic risks were identified, using a checklist, together with a survey of workers to determine the incidence of accidents and incidents to which they have been exposed during their workday. The physical risks found were: noise, light, temperature and humidity, while ergonomic ones; lifting loads, inadequate postures and repetitive movements. After identifying the risks in each job, the risk levels were estimated based on the probability of occurrence, severity of damage, and vulnerability. Once all these activities were carried out, the mínimum occupational risk prevention plan for the Nes Larvas laboratory workers was drawn up, in order to protect physical integrity.